WIA-DM ophthalmologic decision support system based on clinical workflow and data mining techniques. - Ferreira, Edgar da Silva. (2007)
Nowadays one can see a wide application of computer systems in Medicine, especially in data acquisition, registry and supply, constituting the so called Electronic Patient Record (EPR) which allows providing information for advanced consultation and processing. The work described in this report is an integrating part of a project that aims the creation of an innovator system for medical diagnosis support in Ophthalmology, in cooperation with a notable clinic. This system makes use of Data Mining techniques on intelligent analysis and processing of medical data in order to improve all stages of clinical process and to allow a better resource s management. In the course of this project, methods for system integration were researched and developed on a modular software structure that is established on a database for RCE storing. Examination results are imported from medical equipments and saved on this database, which provides structured data to patient management module. Developed software solution already presents the required vigour for testing on clinical environment. Based on spatial and snake filtering, algorithms for processing retinal tomography images were created in order to detect both retinal anterior and epithelium pigment limits. The high success rates reached on image processing allowed integrating it in developed software, as well as getting a vision of Data Mining module.